A desmesura da paixão: reflexões sobre a situação incestuosa - Machado, Érica Prado (2015)
This paper deals with the inter-relation between the sexuality of the perverse adult and the polymorph perverse sexuality of the child, therefore infant, leading into incestuous relations, printing on the infant s psyche, on the daughters of the abuser fathers, the trauma print. Indeed necessary to emphasize that, where there is no mutual agreement, there is invasion, and, therefore, there is abuse, either physical or emotional. For such, I make use of the study and analysis of four clinical cases, of female patients serviced by me in my private clinic. I also comprehend that there is no way of thinking on the meaning of trauma, without pointing to the matter of violence. Although the crucial axis to be debated does not relate of a study about the trauma itself, there is no way to refute the experience of sexual assault, mainly in the childhood or adolescence, is emotionally overwhelming, and, obviously, traumatic. I could note peculiar and characteristic traits on each familiar group, on which I was able to comprehend that the incest issue does not encompass only the father-daughter pair, but indeed englobes a complex weft of unconscious turns that drag for generations (unconscious conflicts between paternal and maternal grandparents), and that leads into the sexual abusive situation. On the incestuous-perverse scene, there is a spectacle of Oedipus Complexes , and of non-crafted conflicts, of all this familiar group. Looking at the incestuous relation is also lean towards the comprehension of the familiar dynamics, and marital relationships. Therefore, this research also builds a reflexion about the conjugality, and, on the study of the familiar psychoanalysis, both within the incestuous situation. Cyrulink (1994) advocates the concept of physical predator by naming the abuser, signalling the desire for present destruction, and endorsing that the usage of the other like a thing-object , perpetrated by the former, has a devastating symbolic effect on his victims. I could conclude that the incestuous family leaves marks on the overwhelming victims of abuse, which can be developed with difficulties, but are not impossible to overcome